Pengaruh Flash Sale, E-WOM, Dan E-Promotion Terhadap Keputusan Pembelian Produk Somethinc Pada Marketplace (Studi Kasus Mahasiswa Universitas Islam Malang) - Nabila, Soraya; Asiyah, Siti; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the influence of flash sales, electronic word of mouth (e-WOM), and e-promotion on the decision to purchase Somethinc beauty products among students at the Islamic University of Malang. The research method used is a quantitative method with data collection techniques through questionnaires. The research results show that flash sales, e-WOM, and e-promotion have a significant influence on purchasing decisions for Somethinc beauty products. This research contributes to the development of digital marketing theory and practice in the beauty industry. The results of this research can be used as a reference for companies to develop effective digital marketing strategies. Keywords: Flash Sale, E-WOM, E-Promotion, Purchase Decision